Where are we with pre‐exposure prophylaxis use in Central and Eastern Europe? Data from the Euroguidelines in Central and Eastern Europe (ECEE) Network Group. Issue 1 (5th October 2020) - Balayan, T; Begovac, J; Skrzat‐Klapaczyńska, A; Aho, I; Alexiev, I; Bukovinova, P; Salemovic, D; Gokengin, D; Harxhi, A; Holban, T; Jevtovic, D; Kase, K; et al.
Abstract : Objectives: Pre‐exposure prophylaxis (PrEP) for HIV infection is an important intervention for control of the HIV epidemic. The incidence of HIV infection is increasing in the countries of Central and Eastern Europe (CEE). Therefore, we investigated the change in PrEP use in CEE over time. Methods: The Euroguidelines in Central and Eastern Europe (ECEE) Network Group was initiated in February 2016 to compare standards of care for HIV and viral hepatitis infections in CEE. Data on access to PrEP were collected from 23 countries through online surveys in May–June 2017 (76 respondents) and in November 2018–May 2019 (28 respondents). Results: About 34.2% of respondents stated that tenofovir/emtricitabine (TDF/FTC) was licensed for use in their country in 2017, and 66.7% that it was licensed for use in 2018 ( P = 0.02). PrEP was recommended in national guidelines in 39.5% of responses in 2017 and 40.7% in 2018 ( P = 0.378). About 70.7% of respondents were aware of "informal" PrEP use in 2017, while 66.6% were aware of this in 2018 ( P = 0.698). In 2018, there were 53 centres offering PreP (the highest numbers in Poland and Romania), whereas six countries had no centres offering PreP. The estimated number of HIV‐negative people on PreP in the region was 4500 in 2018. Generic TDF/FTC costs (in Euros) ranged from €10 (Romania) to €256.92 (Slovakia), while brand TDF/FTC costs ranged from €60 (Albania) to €853 (Finland). Conclusions: Although the process of licensing TDF/FTC use for PrEP has improved, this is not yet reflected in the guidelines, nor has there been a reduction in the "informal" use of PrEP. PrEP remains a rarely used preventive method in CEE countries.